Influence of Online Customer Reviews, Customer Ratings, and E-Servicescape on Trust Affecting Purchase Intention: A Case Study of Marketplaces in Indonesia - A’Yuni, Dinda Qurotun A’Yuni (Universitas Bengkulu, 2023)
This study aims to determine the influence of online customer reviews, customer ratings, and e-servicescape on trust that will affect purchase intention in marketplaces in Indonesia. This research is a type of quantitative research. The method used in this study is the survey method. The population in this study is consumers of marketplace users in Indonesia, with a sample of 305 respondents taken using purposive sampling techniques. Data collection was carried out using the survey method by distributing questionnaires. The data that has been collected is then processed using SEM (structural equation modeling), and analyzed using the SmartPLS (Partial Least Square) program. The results showed that online customer reviews, customer ratings, and e-servicescape have a positive and significant effect on trust in marketplaces in Indonesia. Online customer reviews, Customer rating, e-servicescape, and trust have a positive and significant effect on purchase intention in marketplaces in Indonesia. The results also show that trust mediates the relationship between online customer reviews, customer ratings, and e-servicescape with purchase intention for consumers who will make purchases on marketplaces in Indonesia.